Exploring students' epistemological knowledge of models and modelling in science: results from a teaching/learning experience on climate change. Issue 4 (3rd March 2016) - Tasquier, Giulia; Levrini, Olivia; Dillon, Justin
ABSTRACT: The scientific community has been debating climate change for over two decades. In the light of certain arguments put forward by the aforesaid community, the EU has recommended a set of innovative reforms to science teaching such as incorporating environmental issues into the scientific curriculum, thereby helping to make schools a place of civic education. However, despite these European recommendations, relatively little emphasis is still given to climate change within science curricula. Climate change, although potentially engaging for students, is a complex topic that poses conceptual difficulties and emotional barriers, as well as epistemological challenges. Whilst the conceptual and emotional barriers have already been the object of several studies, students' reactions to the epistemological issues raised by climate changes have so far been rarely explored in science education research and thus are the main focus of this paper. This paper describes a study concerning the implementation of teaching materials designed to focus on the epistemological role of 'models and the game of modelling' in science and particularly when dealing with climate change. The materials were implemented in a course of 15 hours (five 3-hour lessons) for a class of Italian secondary-school students (grade 11; 16–17 years old). The purpose of the study is to investigate students' reactions to the epistemological dimension of the materials, and to explore if and how the material enabled them to develop their epistemological knowledge on models.